2020
DOI: 10.32890/jis.14.2018.8003
|View full text |Cite
|
Sign up to set email alerts
|

Urgency of Political Decentralization and Regional Autonomy in Indonesia: Local Perspectives

Abstract: Indonesia is a country that is inhabited by hundreds of ethnic groups with different geographical condition, natural resources and social culture. Regional decentralization and autonomy that is carried out in Indonesia is an acknowledgment of ethnic diversity (pluralism) to create unity and harmony (BhinekaTunggal Ika), to form social harmony and equal development with the framework of protecting national stability. This article argues on the urgency of political decentralization and regional autonomy in Indon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The implementation of regional autonomy in Indonesia after Indonesia's reformation was marked by the Amendment UUd 1945 process to the Constitution of the Republic of Indonesia and the enactment of Law Number 22 of 1999 concerning Regional Government [7]. The implementation of regional autonomy is the answer to the problems and problems of political centralization, centralization of government authority that is too centralized, administrative centralization and centralization of the economic sector [8].…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of regional autonomy in Indonesia after Indonesia's reformation was marked by the Amendment UUd 1945 process to the Constitution of the Republic of Indonesia and the enactment of Law Number 22 of 1999 concerning Regional Government [7]. The implementation of regional autonomy is the answer to the problems and problems of political centralization, centralization of government authority that is too centralized, administrative centralization and centralization of the economic sector [8].…”
Section: Resultsmentioning
confidence: 99%
“…Based on this conflict of interest, we can say that Indonesia's current form of regional autonomy policy is still not fair. Decentralisation proposes a concept of the division of authority (Yakub, Abdul Ghani, & Anwar, 2020). However, implementing the pattern of division of authority as conceptualised by the decentralisation system has created problems (Hanson, 2022).…”
Section: Conflict Of Interest In the Expansion Of The Sofifi Citymentioning
confidence: 99%
“…Fiscal decentralisation and delegation of authority to local tiers are crucial in improving overall fiscal management. This encourages trust, harmony, and unity in society and proficiently ensures equitable access to basic public needs (Yakub et al, 2018). Zhang (1997) found that economic growth was significantly affected by the distribution of resource structure between local and central governments in the post-1970s reform period.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Fiscal decentralisation and delegation of authority to local tiers are crucial in improving overall fiscal management. It encourages trust, harmony, and unity in society and proficiently ensures equitable access to basic public needs (Yakub et al, 2018). Mobilisation of resources and efficient resource utilisation also result from greater fiscal decentralisation (Baskaran and Feld 2013).…”
Section: Introductionmentioning
confidence: 99%